Športna vzgoja v gimnaziji danes - Beranič, Lovro (Šport (Ljubljana), 2019)
The market logic of modern society is also being transferred to the field of the educational process of today's gymnasium. In Slovenia, we need a new doctrine of sports education in gymnasiums, which also includes theoretical knowledge, which should also be an optional subject in general matura. Such a holistic and anthropologically oriented model of sports education, where it is a balanced exercise of practical sports contents and the transmission of theoretical sports knowledge, puts in the forefront the ideal of the harmoniously developed personality of the adolescent. To this end, we need technologically modern school sports halls and outdoor sports facilities in Slovenia.
Keywords: adolescents; gibalna znanja; gimnazije; gymnasium; mladostniki; motor skills; otroci; sport; sports education; šport; športna vzgoja; teoretična znanja; theoretical knowledge